QAG-TCP Tool for Effective Test Prioritization of Object-Oriented Programs: Design and Implementation - Abubakar, Hassan; Zambuk, Fatima (International Journal of Scientific Research in Computer Science and Engineering, 2025)
Regression testing, a crucial software development phase, can be time-consuming due to the need to re-execute all test cases after code changes. It has been established that Complexity measurement is an essential component for ensuring Software Quality is maintained which in turn determines the success of fault defection in Object- Oriented Program Codes. Lack of complexity measurement mechanism makes some of the existing object-oriented based test case prioritization techniques often not effectively identifying faults early in the testing process. This inefficiency leads to increased testing costs, decrease in Percentage of fault detection, Overall Test Effort in detecting faults, and Average percentage of fault detection rate per cost. In this paper we present an improved technique that handles complexity measurement by incorporating Software Quality measures, the technique will also consider vary fault severity/cost using real faults for Object Oriented programs. This will significantly improve the overall effectiveness in fault detection which will enable developers to identify faults more accurately and efficiently in Object-Oriented Program. The proposed technique is implemented as an automated tool that integrates with existing testing frameworks. Some early results indicates significant improvement